History of Articulators: Henry L. “Harry’’ Page and the Transograph - Fabiana Mansur Varj˜ao, DDS, MSc, PhD1 and (Journal of Prosthodontics, 2006)
Selecting artificial teeth for edentulous patients is difficult when pre-extraction records are not available.